Teaching challenges on the use of storytelling in elementary science lessons - Hajah Nuruljannah Haji Matamit; Roslinawati Roslan; Masitah Shahrill; Hardimah Mohd Said (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study investigated the use of storytelling in teaching elementary science on the topic of ‘Sense Organs’ at the Grade 1 level. A total of 21 students from one of the elementary schools in Brunei Darussalam participated in the study. The qualitative analyses of the observations and video recordings resulted in the classifications of the challenges faced when storytelling was used in the lessons. The four identified categories were the language aspect, development aspect, external challenges and existing knowledge. These categories were then used to investigate further any aspect that would develop the challenges into the teaching and learning of science using storytelling. Despite identifying the challenges in using storytelling in teaching science, storytelling may enhance the students’ understanding of science concepts.